Synthesis and Photophysical Properties of Pyrene-BODIPY Functionalized Subphthalocyanine Dyad - Çetindere, Seda (Mustafa CAN, 2022)
The treatment of boron(III) subphthalocyanine chloride (SubPcCl) with borondipyrromethene (BODIPY) derivative consisting one pyrene group in toluene gave the corresponding axially substituted boron(III) subphthalocyanine dyad (SubPcBodiPy). Novel compound has been fully characterized by FTIR, mass, NMR (1H and 13C) spectroscopy and elemental analysis. Photophysical properties of SubPcBodiPy was investigated and compared with its precursors by fluorescence and absorption spectroscopy in THF. Accordingly, fluorescence lifetimes were measured directly by single exponential calculation.

The treatment of boron(III) subphthalocyanine chloride (SubPcCl) with borondipyrromethene (BODIPY) derivative consisting one pyrene group in toluene gave the corresponding axially substituted boron(III) subphthalocyanine dyad (SubPcBodiPy). Novel compound has been fully characterized by FTIR, mass, NMR (1H and 13C) spectroscopy and elemental analysis. Photophysical properties of SubPcBodiPy was investigated and compared with its precursors by fluorescence and absorption spectroscopy in THF. Accordingly, fluorescence lifetimes were measured directly by single exponential calculation.
Keywords: Chemical Engineering; Kimya Mühendisliği